Improving growth and yield of okra by intercropping with varying populations of legumes - Ajayi, Oluwakayode Emmanuel; OKONJI , Christopher John; AYANLOLA , Olamide Tubosun; OLOFINTOYE , Temidayo A. Joseph; Oyelowo, Deborah (Journal of Agricultural Sciences (Belgrade), 2020)
An experiment was conducted at the Vegetable Research Farm of National Horticultural Research Institute, Ibadan, Oyo state, Nigeria, in the rain-forest agro-ecological zone in 2016 and 2017 to determine suitable cropping systems to increase yield of okra. Seed of okra (Abelmoschus esculentus (L.) Moench), cv. LD-88, was planted at a spacing of 60 × 40 cm as an inter- and monocrop to produce an average density of 4.2 plants∙m-2; the intercrops cowpea [Vigna unguiculata (L.) Walp.], var. Ife brown, and peanut (Arachis hypogaea L.), var. Kampala, were planted at spacings to provide an average densities of 5.6 plants∙m-2, 4.2 plants∙m-2, 3.3 plants∙m-2 and 2.7 plants∙m-2. Data were collected on plant height, number of leaves, leaf area, stem diameter and fruit yield of okra. Year affected plant height, number of leaves, leaf area, stem diameter and fruit yield of okra intercropped with legumes at different densities. Legume densities affected plant height, number of leaves and stem diameter leaf area and fruit yield. Year × legume densities interaction affected plant height, number of leaves, stem diameter, leaf area and fruit yield of okra. Intercropping okra with peanut at density of 2.7 plants∙m-2 enhanced its growth and yield and appears to be the best configuration for these crops.